THE BANALIZATION OF THE VIOLENCE IN CAIO FERNANDO DE ABREU - Castro Alves Muranaka, Larissa Camargo [UNESP] (Univ Estado Mato Grosso, 2022)
The marginal discourse is a movement coming from the periphery, where the subjects that make up this space denounce, through art, the degrading environment in which they live. The main objective of this article is to search in the specific context of Caio Fernando Abreu's literature, the ideological relations that surround the interior of the narrative plan, discussing the marginal voices that echo in the great urban centers, from a conflict established between the reality experienced by the marginalized in confrontation with the bourgeois reality. In the line that Antonio Candido and Alfredo Bosi called fierce realism (BOSI, 1986), the author incisively reveals homosexual relationships and the subversiveness of their character at the time, the trivialization of violence and the marginalization to which it presents itself in different forms in the short stories Morangos Mofados and Terca-Feira Gorda. Urban violence, in fact, constitutes Caio's literature. A theme that installs and dialogues with contemporaneity.
Keywords: Caio Fernando Abreu; Marginal discourse; Banalization of violence